Seasonally and regionally determined indication potential of bioassays in contaminated river sediments - Hilscherová, Klára; Dusek, Ladislav; Sídlová, Tereza; Jálová, Veronika; Cupr, Pavel; Giesy, John P; Nehyba, Slavomír; Jarkovský, Jirí; Klánová, Jana; Holoubek, Ivan (Environmental toxicology and chemistry, 2010)
River sediments are a dynamic system, especially in areas where floods occur frequently. In the present study, an integrative approach is used to investigate the seasonal and spatial dynamics of contamination of sediments from a regularly flooded industrial area in the Czech Republic, which presents a suitable model ecosystem for pollutant distribution research at a regional level. Surface sediments were sampled repeatedly to represent two different hydrological situations: spring (after the peak of high flow) and autumn (after longer period of low flow). Samples were characterized for abiotic parameters and concentrations of priority organic pollutants. Toxicity was assessed by Microtox test; genotoxicity by SOS-chromotest and green fluorescent protein (GFP)-yeast test; and the presence of compounds with specific mode of action by in vitro bioassays for dioxin-like activity, anti-/androgenicity, and anti-/estrogenicity. Distribution of organic contaminants varied among regions and seasonally. Although the results of Microtox and genotoxicity tests were relatively inconclusive, all other specific bioassays led to statistically significant regional and seasonal differences in profiles and allowed clear separation of upstream and downstream regions. The outcomes of these bioassays indicated an association with concentrations of polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) as master variables. There were significant interrelations among dioxin-like activity, antiandrogenicity and content of organic carbon, clay, and concentration of PAHs and PCBs, which documents the significance of abiotic factors in accumulation of pollutants. The study demonstrates the strength of the specific bioassays in indicating the changes in contamination and emphasizes the crucial role of a well-designed sampling plan, in which both spatial and temporal dynamics should be taken into account, for the correct interpretations of information in risk assessments.
Keywords: Organic Chemicals; polycyklické aromatické uhlovodíky; Rivers; Water Pollutants, Chemical; geologické sedimenty; Aliivibrio fischeri; polychlorované bifenyly; řeky; roční období; Biological Assay; Polycyclic Aromatic Hydrocarbons; Seasons; biotest; organické látky; Geologic Sediments; chemické látky znečišťující vodu; Polychlorinated Biphenyls